Rpn13p and Rpn14p are involved in the recognition of ubiquitinated Gcn4p by the 26S proteasome - Seong, Ki Moon; Baek, Je-Hyun; Yu, Myeong-Hee; Kim, Joon (ELSEVIER SCIENCE BV, 2007)
The 26S proteasome, composed of the 20S core and 19S regulatory complexes, is important for the turnover of poly-ubiquitinated proteins. Each subunit of the complex plays a special role in proteolytic function, including substrate recruitment, deubiquitination, and structural contribution. To assess the function of some non-essential subunits in the 26S proteasome, we isolated the 26S proteasome from deletion strains of RPN13 and RPN14 using TAP affinity purification. The stability of Gcn4p and the accumulation of ubiquitinated Gcn4p were significantly increased, but the affinity in the recognition of proteasome was decreased. In addition, the subcomplexes of the isolated 26S proteasomes from deletion mutants were less stable than that of the wild type. Taken together, our findings indicate that Rpn13p and Rpn14p are involved in the efficient recognition of 26S proteasome for the proteolysis of ubiquitinated Gcn4p. (c) 2007 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: TRANSCRIPTION FACTOR GCN4; SACCHAROMYCES-CEREVISIAE; DEUBIQUITINATING ENZYME; PROTEIN; YEAST; DEGRADATION; SUBUNIT; PROTEOLYSIS; TURNOVER; COMPLEX